OSTRICHES AND GEOTOURISM: THE EVOLUTIONARY PATHWAY OF A SMALL TOWN TOURISM DESTINATION IN SOUTH AFRICA - Christian M. ROGERSON; Jayne M. ROGERSON (Geo Journal of Tourism and Geosites, 2024)
Small towns are a critical tier in the settlement hierarchy. For many small towns tourism is a vital sector of local development. This paper contributes an historical perspective on small town destination development. Using archival sources the paper provides a window on the evolutionary development of one small town tourism destination in South Africa. The case study is Oudtshoorn in the Western Cape. During the late 19th century and early 20th century Oudtsthoorn experienced phases of economic boom and bust which linked to international fashion and the trade in ostrich feathers. The imprint of this era is manifest in the town’s landscape of ‘feather palaces’. In terms of early 20th century tourism growth it is demonstrate d geotourism was a critical driver with the asset of Cango Caves. In the period after the Second World War, the local tourism economy diversifies with the revival and reorientation of ostrich farming which incorporates ostriches as tourism attractions. The evolutionary pathway of this small town changes such that its local tourism economy is anchored on the dual foundations of its geotourism and ostrich attractions.